Temporal dynamics in the effectiveness of seed dispersal by birds visiting a tropical tree - Pizo, Marco A. [UNESP]; Camargo, Paulo H. S. A. [UNESP] (Cambridge University Press (CUP), 2018)
Seed dispersal effectiveness (SDE) is related to the role of seed dispersal agents in realizing the reproductive potential of plants through seed dispersal and subsequent plant recruitment. The SDE of a given seed disperser may vary spatially and temporally, with important implications for our understanding of the mutualistic relationships involving plants and frugivores. Here we observed 22 frugivorous bird species visiting an individual tree (Cabralea canjerana) over a 9-y period in a fragment of Atlantic forest in south-eastern Brazil to document the temporal variation in SDE. The quantitative (that takes into account the frequency of feeding visits to the focal plant and the number of fruits removed per visit) and qualitative (that considers the probability of seed deposition on a suitable site for plant recruitment) components of SDE varied in two and one order of magnitude both among bird species and among years within bird species, respectively. As a result, the SDE of bird species fluctuates over the years, especially for a migratory species that is the main seed disperser of C. canjerana (Chivi vireo Vireo chivi) whose quantitative component (i.e. the product of visit and fruit intake rates) varied from 3.0 to 7.1. This study illustrates the dynamic nature of the seed-dispersal environment to which a plant is subjected to over the course of its life, which has important consequences for the plant's individual fitness.
Keywords: agonistic interactions; Atlantic forest; Cabralea canjerana; forest fragmentation; frugivory; fruit chemistry